Performance experiment and numerical prediction on the optimization design of the micro-sized water turbine for the hose reel irrigator - Tang, Lingdi; Yuan, Shouqi; Tang, Yue; Yan, Haofang (International Journal of Agricultural and Biological Engineering, 2018)
In order to significantly improve the efficiency of driving water turbine used in hose reel irrigator, a new water turbine structure was proposed by the method of performance test and numerical calculation. The internal flow characteristics of original water turbine were analyzed, and it was found that unreasonable design of main flow passage components such as inlet, outlet and runner could not effectively translated pressure energy of upper stream into impact kinetic energy of blade, and gave rise to low energy conversion efficiency of water turbine. The inadequate internal flow and uneven pressure distribution were also not conducive to energy conversion efficiency. Then a new structure of water turbine structure was presented, in which the inlet has a tangential nozzle jet and the outlet is in axial direction. The computational analysis showed that the nozzle jet at the inlet of the new water turbine runner, which makes jet flow mainly concentrate in the impacted blade passage, can reduce the loss of flow kinetic energy. The axial outflow increases the distance of inflow in the runner, which is more conducive to the runner blades work. Performance experiments on both original and new water turbines showed that the highest efficiency of the new turbine is almost 20 percentages higher than that of the original turbine, and the new turbine is nearly triple output power over the original turbine. The internal flow characteristic analysis and the performance experiment were conducted to assess the feasibility of the replacement of the original water turbine by the new water turbine. Keywords: micro-sized water turbine, hose reel irrigator, optimization design, experimental study, numerical analysis DOI: 10.25165/j.ijabe.20181105.2876 Citation: Tang L D, Yuan S Q, Tang Y, Yan H F. Performance experiment and numerical prediction on the optimization design of the micro-sized water turbine for the hose reel irrigator. Int J Agric & Biol Eng, 2018; 11(5): 108–115.